Pengaruh Terapi Akupresur terhadap Tingkat Kecemasan pada Ibu Hamil Trimester III - Ita Novianti; Asrianti Safitri Muchtar (Poltekkes Kemenkes Palu, 2021)
Introduction: The prevalence of pregnancy anxiety is around 14-54%, highest in the first and third trimesters. Acupressure attracts attention as a non-pharmacological therapy for natural relaxation. The research aims to determine the effect of acupressure therapy on anxiety levels. Method: This study was conducted at the Health Centers of Tamalanrea Jaya and Antang, the study used a quasi-experimental design with the pre and post test approach in the intervention group and the control group. The total of research subjects 40 trimester III pregnant mothers who had experience anxiety. The intervention group (21 samples) with acupressure therapy and the control group (19 samples) with placebo therapy. Measuring anxiety using the Hamilton Anxiety Rating Scale (HARS). Result: in the intervention group, the mean of anxiety before the intervention was 26.6 and after the intervention was 22.3 (p value <0.001), while in the control group it was 26.1 before and 25.1 after the intervention (p value = 0.072). The mean reduction in pregnancy anxiety level in the intervention group was more significant than the control group. Conclusion: Acupressure therapy has a significant effect on decreasing anxiety levels in pregnant mothers in the intervention group (p<0.001) and acupressure therapy can be used as one of the effective non-pharmacological methods to reduce symptoms of anxiety in pregnancy.